Monitoring and evaluation practices in selected non governmental organisations - Chibonore, Wilma Claris (My University, 2016)
Monitoring and Evaluation (herein referred to as M&E) has become a critical practice in the delivery and improvement of development programmes in many Non-Governmental Organisations (herein referred to as NGOs). This study explored M&E practices in NGOs. The study adopted a qualitative research approach that allowed the researcher to capture participants’ lived experiences. A case study design was used. The sample size was made up of 8 different Non-Governmental Organisations in Gauteng. From the first two organisations two participants were chosen from each, then one participant was chosen from each of the other six organisations. This gives a total of 10 project/programme managers who were interviewed. Also, two key informants of the study were drawn from people who are experts in the M&E sector by academic qualification and experience who were working as M&E specialists in corporate companies that conduct advanced M&E for NGOs as hired consultancies. These are the participants who were able to offer comprehensive answers that were directly relevant to the purposes of the research. Participants were purposively selected and in-depth interviews guided by the use of semi-structured interview schedules were used to collect data. Thematic content analysis was used to analyse data. The findings of the study reveal that factors such as management style of engagement and donor expectations influence the design of M&E systems. Challenges faced by practitioners in the design and implementation of M&E systems include among other things poor implementation of plans, shortage of personnel who are competently trained to undertake M&E, less funding allocated to M&E and performing M&E as a ritual rather than an important subcomponent of good project management. The findings of this research contribute to our understanding M&E practices in NGOs. It is hoped that insights gleaned in the study will help to inform both practice and theory in this area of inquiry
A research report presented to the Department of Social Work School of Human and Community Development Faculty of Humanities University of the Witwatersrand In partial fulfillment of the requirements for the Master of Arts by Coursework and Research Report in Social Development, November 2015
Keywords: Non-governmental organizations--South Africa--Management; Nonprofit organizations--South Africa--Management; Project management--South Africa; Evaluation research (Social action programs)